(untitled) (Philological Studies, 2019)
The article presents a widespread indo-European and worldwide fairytale motif of the external or separate/separable soul in a Serbian and a Russian fairytale. Both antiheros Bash Chelik and Koschei the Deathless are immortal for their souls are hidden in a secret place. As long as their soul stays untouched, they are invincible. As we tend to demonstrate by presenting the context of cosmogonic symbols, the place where their soul is hidden is of right the locality of the beginning of the Universe and life itself.